Early Careers of Dropouts from Vocational Training: Signals, Human Capital Formation, and Training Firms. (25th June 2020) - Patzina, Alexander; Wydra-Somaggio, Gabriele
Abstract: Dropping out of post-secondary education has negative consequences for career progression. However, as human capital theory predicts and as previous studies have shown, having some training still pays off. For a large part of the European workforce who has attended vocational training, however, the theoretical predictions are less clear and empirical studies are scarce. In occupational labour markets, signalling and credentialism theories predict negative effects of dropping out. Furthermore, apprenticeship dropouts learn at different training firms, which differ in their influence on human capital development and the provision of job opportunities. Relying on a unique panel data set from Germany and estimating normalized fixed effects growth curve estimators, our study reveals the following results. First, the timing of dropping out structures career progression, as late dropouts have the highest employment rates and highest wages within the dropout population. However, in an occupational labour market setting, credentials and signals are still highly important for career progression, as the wage advantage of late dropouts within the dropout population is rather small, and late dropouts suffer a wage penalty when we compare their wage profiles to those of graduates. Second, our study emphasizes the importance of training firms, which influence the human capital development of individuals during the course of training and provide dropouts with connections to their first jobs. Thus, in occupational labour markets, the consequences of dropping out depend mainly on different mechanisms, as in other settings.